2020
DOI: 10.1177/1757913920948916
|View full text |Cite
|
Sign up to set email alerts
|

Participatory visual arts activities for people with dementia: a review

Abstract: Aims: To report and summarise the effects of interventions using participatory visual arts activities in dementia research through a narrative synthesis systematic review. Methods: We searched four databases MEDLINE, EMBASE, PsycINFO and Applied Social Sciences Index & Abstracts (ASSIA). Of the 3263 records retrieved, 20 were included in this review. Quality was assessed with the Critical Appraisal Skills Programme (CASP) and the Downs and Black checklist. Results: The use of participatory visual arts has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A significant number of art reviews (41%) have been performed in the past 10 years. The art reviews focused on visual arts ( Chancellor et al, 2014 ), participatory arts ( Zeilig et al, 2014 ; Ward et al, 2020 ; Cavalcanti Barroso et al, 2022 ), classified creative arts under the umbrella term of art therapy ( Beard, 2011 ), or nonpharmacological interventions ( Brown Wilson et al, 2019 ). The remaining creative arts were represented as music (27%), dance (23%), psychosocial (4%), and sensory (5%) interventions.…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of art reviews (41%) have been performed in the past 10 years. The art reviews focused on visual arts ( Chancellor et al, 2014 ), participatory arts ( Zeilig et al, 2014 ; Ward et al, 2020 ; Cavalcanti Barroso et al, 2022 ), classified creative arts under the umbrella term of art therapy ( Beard, 2011 ), or nonpharmacological interventions ( Brown Wilson et al, 2019 ). The remaining creative arts were represented as music (27%), dance (23%), psychosocial (4%), and sensory (5%) interventions.…”
Section: Resultsmentioning
confidence: 99%
“…People with dementia and AD need stimulation to retain capabilities, perhaps at a different level, but none the less they are deserving of novel but guided experiences. Barroso et al, (2020) share that people with dementia need to be active and engaged in meaningful activities such as visual art, which contribute to enhanced quality of life for this population. As dementia progresses, people have fewer opportunities to participate in activities independently and therefore need support with daily life activities.…”
Section: Discussionmentioning
confidence: 99%
“…As dementia progresses, people have fewer opportunities to participate in activities independently and therefore need support with daily life activities. Visual art interventions make it possible for people with dementia to experience improved social connectedness and wellbeing (Barroso et al, 2020). Savazzi et al, (2020) conducted a quasi-experimental study to examine effects of a multi-dimensional visual art intervention on people with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, art galleries and museums around the world have developed access programs to provide art activities for people with dementia. Often developed in partnership with health, dementia support or aged care services, these access programs have the potential to enhance the psychosocial and psychophysiological wellbeing of people with dementia, providing an opportunity for intellectual stimulation, creative engagement, social interaction, and personal reflection (Camic et al, 2016; Cavalcanti Barroso et al, 2022; D'Cunha et al, 2020; Ullán et al, 2013). A taxonomy of arts interventions for people with dementia listed eight principles and features: transformation, possibility, connection, expression, involvement, selfhood, humanity, and engagement (Cousins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A decade ago, Beard (2012) identified that within the literature relating to art and dementia, there is a distinction to be made between art therapy (a form of psychotherapy that generally occurs in clinical settings and is delivered by licensed therapists) and art activities (with a focus on engaging in art or with the arts as a creative, social and leisure activity). Following this distinction, these access programs are art activities rather than art therapy, although such programs may have a range of therapeutic benefits (Cavalcanti Barroso et al, 2022; D’Cunha et al, 2019; Young et al, 2015). Ward et al (2021) describe such activities as participatory art activities that take place in community settings and are delivered by art professionals.…”
Section: Introductionmentioning
confidence: 99%